Linguistic analysis of writing errors in non-Persian speaking Iranian students: Evidence from audiences of Roshd magazines - Seyyed Bahnām Alavi Moghaddam; Ma’sume Kheirābādi (فصلنامه نوآوری‌های آموزشی, 2012)
In its simplest definition, literacy means obtaining the ability to read and write in official language. Although most students try to get mastery on the two mentioned language arts; however, for students of non-Farsi speaking districts, education of Farsi as an official language has more limitations and difficulties. In the process of learning a second or foreign language, errors are considered as natural phenomena. Error Analysis (EA) is a method for indentifying educational needs in order to improve the quality of materials and techniques of education. Error Analysis means the comparison of sentences (written or oral) produced by learners with the sentences of native speakers according to their adjustment/non-adjustment with rules of language under study. In this research, written errors of non-Persian speaking students (Turk students learning Farsi as a second Language) of the intermediate and advanced levels have been analyzed. The body of the data were gathered from the letters and manuscripts of Iranian students writing to Roshd magazines and they were described and analyzed using descriptive method. They contained 100 error items which were categorized in four groups: orthographic (spelling), morphological (Lexical), structural and pragmatic errors. The aim of this research was finding the most frequent errors in the writing of non-Persian speaking Iranian students. The results showed that the most frequent type of errors is structural one (containing 72% of all the errors). In other words, Iranian non-Persian speaking students generally do have more problems and deficiencies in application of Persian grammatical rules in their writings. Consequently material developers and textbook authors should pay more attention to this finding especially while developing textbooks and educational aids for this group of students.